STANDARISASI DAN DASAR PIJAKAN ETIKA KOMUNIKASI DAKWAH - Ariani, Anita (UIN Antasari Banjarmasin, 2015)
Ethics becomes the foundation to communicate between individuals and groups. Ethics provide a moral foundation in building deontology against all attitudes and behavior of individuals or groups in communication. standardization and communication ethics propaganda foundation is built on the instructions of communication Ethics Koran, Islam teaches that communicates with a full civilized, respectful, respect for people who talk, and so on. When talking with others, Islam provides a clear foundation on procedures speaking namely: qawlan sadidan correct word meaning contained in the Koran letter an-Nisa verse 9 and Al-Ahzab verse 70, qawlan balighan means striking the words contained in the letter of an- Nisa verse 63, qawlan maysuran means the word is found in the Quran surah Al-Isra verse 28, qawlan layyinan meaning words of gentle contained in the Quran letter Lugman paragraph 44, qawlan Kariman meaning words that glorious contained in the Quran surah Al-Isra verse 23 and qaulan ma'rufan appropriate word meaning contained in the Koran letter an-Nisa verse 5.Etika menjadi dasar pijakan berkomunikasi antara individu dan kelompok. Etika memberikan landasan moral dalam membangun tata susila terhadap semua sikap dan perilaku individu atau kelompok dalam komunikasi. standarisasi dan dasar pijakan etika komunikasi dakwah adalah Etika komunikasi dibangun berdasarkan petunjuk Alquran, Islam mengajarkan berkomunikasi itu dengan penuh beradab, penuh penghormatan, penghargaan terhadap orang yang diajak bicara, dan sebagainya. Ketika berbicara dengan orang lain, Islam memberikan landasan yang jelas tentang tata cara berbicara yaitu: qawlan sadidan artinya perkataan yang benar terdapat pada quran surat an-Nisa ayat 9 dan Al-Ahzab ayat 70, qawlan balighan artinya perkataan yang mengena terdapat pada surat an-Nisa ayat 63, qawlan maysuran artinya perkataan yang mudah terdapat pada quran surat Al-Isra ayat 28, qawlan layyinan artinya perkataan yang lembut terdapat pada quran surat Lugman ayat 44 , qawlan kariman artinya perkataan yang mulia terdapat pada quran surat Al-Isra ayat 23 dan qaulan ma?rufan artinya perkataan yang pantas terdapat pada quran surat anNisa ayat 5